2018
DOI: 10.1177/0264619618780914
|View full text |Cite
|
Sign up to set email alerts
|

Teaching pedagogies in Tanzanian inclusive educational settings: Do they respond to diverse needs? Voices from students with visual impairment

Abstract: Students' learning and participation in inclusive educational settings requires, among other things, teaching pedagogies that respond to students' diverse needs so as to benefit from the education provided. This study explored teaching pedagogies employed in Tanzanian inclusive educational settings across all educational levels, whether or not they respond to students' diverse needs, using voices of students with visual impairment (VI) in higher education institutions (HEIs). A total of 16 students with VI fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Findings indicated that most primary school teachers lacked appropriate theoretical and practical knowledge and skills to design inclusive lessons, adapt the curriculum in terms of objectives, content, learning activities, learning materials, assessment and learning environment to cater for diverse learners' in Kenya, Chireshe (2013) in Zimbabwe, Dalton et al (2012) in South Africa who reported that majority of trained teachers lack knowledge and skills for handling learners with SENs in inclusive classrooms. Kisanga and Richards (2018) in Tanzania reported that teachers had inadequate knowledge and skills for implementing IE. Likewise, they did not modify the curriculum or use IEPs to meet the educational needs of pupils with disabilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings indicated that most primary school teachers lacked appropriate theoretical and practical knowledge and skills to design inclusive lessons, adapt the curriculum in terms of objectives, content, learning activities, learning materials, assessment and learning environment to cater for diverse learners' in Kenya, Chireshe (2013) in Zimbabwe, Dalton et al (2012) in South Africa who reported that majority of trained teachers lack knowledge and skills for handling learners with SENs in inclusive classrooms. Kisanga and Richards (2018) in Tanzania reported that teachers had inadequate knowledge and skills for implementing IE. Likewise, they did not modify the curriculum or use IEPs to meet the educational needs of pupils with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…More so, previous studies focused on secondary and higher education levels. Studies conducted in Tanzania concentrated on the general challenges facing the implementation of IE, focusing on students with intellectual, visual or hearing impairments (Cosmas 2016;Kisanga 2017;Kisanga and Richards 2018;Magige 2017;Ntiruka 2016). They fail to enlist particularly pedagogical practices in the inclusion of pupils with moderate deafblindness, which according to Herbster, (2015) and Wolsey (2017), empirical evidence is limited and scattered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem retards learning abilities of students with visual impairment by making them fail in inal examinations (Kisanga, 2019;POSSI & MILINGA, 2017). Moreover, such situation makes them remain marginalized in the education sector thereby preventing them from proceeding with further studies, competing effectively in the labour market, developing their independence for better living in future, and beneiting from other advantages of studying secondary education (King, 2014;Kisanga & Richards, 2018).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Consequently, student numbers in public schools have progressively increased. Previous studies [31][32][33][34][35][36][37][38] pointed out valuable guidelines for enhancing the learning environment to promote the inclusion of students who are with visual impairment. These guidelines can be summarized as follows:…”
Section: Introductionmentioning
confidence: 99%